Lactiplantibacillus plantarum-encapsulated microcapsules prepared from okra polysaccharides improved intestinal microbiota in Alzheimer’s disease mice - Hsiao, Yao-Kun; Lee, Bao-Hong; Wu, She-Ching (Frontiers in Microbiology, 2024)
Background: Okra contains a viscous substance rich in water-soluble material, including fibers, pectin, proteoglycans, gum, and polysaccharides. This study explored the use of okra polysaccharides by microorganisms and their potential to improve microbiota.The regulation of okra polysaccharides prepared-microcapsules with or without L. plantarum encapsulation on intestinal microbiota was assessed through 16S metagenomic analysis and short-chain fatty acids (SCFAs) in APP NL-G-F/NL-G-F mice (Alzheimer's disease; AD model).We found that Lactobacillaceae and Lactobacillus were majorly regulated by okra polysaccharides prepared-microcapsules in AD mice. Similarly, okra polysaccharides preparedmicrocapsules with L. plantarum encapsulation markedly elevated the abundance of Lactobacillaceae and Lactobacillus, and increased SCFAs in AD mice.Our results suggest that okra polysaccharides prepared-microcapsules with or without L. plantarum encapsulation may improve intestinal microbiota by elevating Lactobacillus levels in AD mice.